2021
DOI: 10.1038/s41467-021-22290-1
|View full text |Cite
|
Sign up to set email alerts
|

Direct detection of coupled proton and electron transfers in human manganese superoxide dismutase

Abstract: Human manganese superoxide dismutase is a critical oxidoreductase found in the mitochondrial matrix. Concerted proton and electron transfers are used by the enzyme to rid the mitochondria of O2•−. The mechanisms of concerted transfer enzymes are typically unknown due to the difficulties in detecting the protonation states of specific residues and solvent molecules at particular redox states. Here, neutron diffraction of two redox-controlled manganese superoxide dismutase crystals reveal the all-atom structures… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(104 citation statements)
references
References 77 publications
10
56
0
Order By: Relevance
“…To this end, Azadmanesh and coworkers collected roomtemperature neutron diffraction data from oxidized Mn(III)SOD and reduced Mn(II)SOD to resolutions of 2.20 and 2.30 Å , respectively (Azadmanesh et al, 2021). The heavyatom positions of the MnSOD backbone and side chains were determined using X-ray data sets of the reduced and oxidized forms and these coordinates were used as the starting models for neutron data-only refinement to avoid including X-rayinduced artefacts at the manganese centre.…”
Section: Manganese Superoxide Dismutasementioning
confidence: 99%
See 2 more Smart Citations
“…To this end, Azadmanesh and coworkers collected roomtemperature neutron diffraction data from oxidized Mn(III)SOD and reduced Mn(II)SOD to resolutions of 2.20 and 2.30 Å , respectively (Azadmanesh et al, 2021). The heavyatom positions of the MnSOD backbone and side chains were determined using X-ray data sets of the reduced and oxidized forms and these coordinates were used as the starting models for neutron data-only refinement to avoid including X-rayinduced artefacts at the manganese centre.…”
Section: Manganese Superoxide Dismutasementioning
confidence: 99%
“…The role of Tyr34 as a proton donor to WAT1 was further put into question by the finding that in the manganese(III) form Tyr34 is deprotonated, forming an SSHB with a neighbouring WAT2 molecule, ruling out its role as a proton donor The active site of manganese superoxide dismutase. (a) The oxidized active site with a doubly protonated Gln143 (PDB entry 7kks, perdeuterated; Azadmanesh et al, 2021). 2F o À F c NSLD map ( = 1.00) is displayed as a blue mesh; H and D atoms are displayed in white and turquoise, respectively.…”
Section: Manganese Superoxide Dismutasementioning
confidence: 99%
See 1 more Smart Citation
“…[29] Manganese, one of the trace elements that is essential for human health, has been reported to be a necessary constituent of metalloenzyme. [30] Moreover, manganese exhibits good biocompatibility and can easily degrade in organisms; these properties are of vital importance for biological application. [31] Previous studies have reported that the enzyme activity of nanozyme is associated with a change in size, [19] chemical composition, [32] morphology, [33][34][35] and surface coating.…”
Section: Introductionmentioning
confidence: 99%
“…Neutron macromolecular crystallography (NMX) is the technique of choice for determining the position of hydrogen atoms and the protonation state of active groups [14][15][16] that are involved in the catalytic activity of enzymes or the binding of a ligand to a macromolecule [17][18][19][20] . Moreover, neutrons do not cause any radiation damage to the biological sample so the structure determination and data collection can be performed at room temperature (RT), giving a more accurate view of local flexibility and water mobility at biologically relevant temperatures 21,22 .…”
Section: Introductionmentioning
confidence: 99%